Management of Students' Self-Acceptance of Body Image: A Case in a Seventh Grade Junior High School Student - Nikene Sampin; Nurussakinah Daulay (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study sought to elucidate the phenomena that determine body images, such as discontent with body shape, the impact of dissatisfaction with body shape, and the impact of efforts to overcome body image dissatisfaction in college students. During the observation in the eighth grade of State Junior High School 6 Percut Sei Tuan, the researcher also saw some kids with low self-acceptance. The method employed is descriptive, and the research is qualitative. The Miles and Huberman model was utilized for data analysis; it is an interactive model that includes data reduction, data display, and generating conclusions. The findings revealed: (1) Low self-acceptance of body image among eighth pupils at State Junior High School 6 Percut Sei Tuan. Some students still believe their physical condition and body form are less desirable. It causes a sense of insecurity. Students' mistrust motivates them to improve their physical condition and body form. (2) The influence of acceptable body image on the conduct of eighth-grade students at State Junior High School 6 Percut Sei Tuan can disrupt student learning continuity. as if oblivious to his lesson. It is because these pupils lack the courage to express themselves in class. It, of course, significantly impacts the efficacy of student learning in the classroom. It has a significant impact on the efficacy of student learning. (3) The Counseling Guidance teacher attempts to cultivate self-acceptance in students' body image. The Counseling advice instructor gives students who require follow-up services on the topic of low self-acceptance and body image with information, group advice, group counseling, and individual counseling.